Optimization of Mangrove Ecosystem Management in Kawasan Bungkutoko, Southeast Sulawesi as Ecotourism Area - Agus Salim; Risma Illa Maulany; Ngakan Putu Oka (Jurnal Hutan dan Masyarakat, 2020)
This study aims to determine (1) Assessment of Bungkutoko Ecotourism Conditions; and (2) Supporting factors for optimizing management, and (3) strategies for optimizing management. This research will be carried out for three months from September to December 2018 in the Bungkutoko mangrove tracking ecotourism area, Kendari City, Southeast Sulawesi (Figure 1). Identification of unknown mangrove species will be carried out at the Laboratory of Conservation of forest resources and ecotourism, Faculty of Forestry, Hasanuddin University. The results of the study: (1) Biophysical potential of mangrove ecotourism in Bungkutoko, namely 8 species of mangrove plants consisting of Avicennia lanata, Rhizophora stylosa, Bruguiera gymnorrhiza, Rhizophora apiculata, Sonneratia alba, Xylocarpus granatum, Xylocarpus stylosa, Bruguiera gymnorrhiza, Rhizophora apiculata, Sonneratia alba, Xylocarpus granatum, Xylocarpus stylosa, Bruguiera gymnorrhiza, Rhizophora apiculata, Sonneratia alba, Xylocarpus granatum, Xylocarpus moluccensis, L faustis and L faecus, and Lizar. from birds and reptiles. (2) Condition of mangrove ecotourism practices in Bungkutoko Not optimal, both in terms of education, conservation and welfare. (3) The ecotourism development strategy in Bungkutoko is in quadrant II (S-T strategy). The strategies formulated in quadrant II include: increasing the availability of educational facilities, increasing efforts to preserve the environment of mangrove forests, empowering local communities, increasing Human Resources, and working with the Kendari city government and the private sector to add infrastructure.